Epidemiological and clinical characteristics of congenital cardiopathies in children under 5 in Hospital Almanzor Aguinaga Asenjo. January - December 2012 - Uribe Rivera, Ana Karla (2015)
Objective: Identify the epidemiological and clinical characteristics of congenital cardiopathies in children under 5 in "Almanzor Aguinaga Asenjo's" Hospital during January - December 2012. Material and Methods: Quantitative descriptive cross sectional study design, the chosen were children under 5 years who were diagnosed with congenital cardiopathies in "Almanzor Aguinaga Asenjo's" Hospital between January to December 2012, data were obtained from the Hospital Management System using the ICD-10 (Q00 -Q99) in the area of Health Intelligence of "Almanzor Aguinaga Asenjo's" Hospital and obtained a list of which doctors office requested medical records for making database in Excel 2010. Results: 109 patients, predominantly male (55%) between 6 months and 2 years (40 %) from Lambayeque (55%), predominated acyanotic congenital cardiopathies (92%), ventricular septal defect (VSD ) , atrial septal defect (ASD ) and patent ductus arteriosus (PCA ) the most common, whereas cyanotic congenital heart disease (8 % ) , 56% represented by Tetralogy of Fallot. Treatment, 38% with drug treatment, 22% observation and 40% surgical treatment. Conclusion: The most prevalent congenital heart disease in the Almanzor Aguinaga Asenjo's Hospital are similar to those reported in national and international literature. More frequently in males, from Lambayeque and of the acyanotic type, being the interventricular communication most frequently, and treatment prevails conservative, observation and pharmacological depending on hemodynamic stability.